Performance of polymer electrolyte membrane for polymer electrolyte fuel cell membrane made with supramolecular structure. (March 2019) - Hendrana, S; Indayaningsih, N; Sudirman
Abstract: Most of membranes for Polymer Electrolyte Membrane Fuel Cell (PEMFC) are made by clustering sulfonate groups which part of hydrophobic portion. The portion then acts as proton conduction path by assistance of water absorbed in the membrane. In this work, the membrane is prepared based on constructing supramolecular structure by aligning sulfonate groups in sulfonated polystyrene (SPS) through formation of hydrogen bond of anhydride pendant group of polyethylene- graft -maleic anhydride (PE- g -MA). The performance was evaluated with many factors, i.e. addition of addition of benzimidazole, and effect of morphology. The addition of benzimidazole have tendency to modify hydrogen interaction within the membrane. In addition, water, which facilitates proton conduction, would also give a small microstructural change in membrane. However, the membrane could maintain its performance which is indicated by its ionic conductivity.